2016
DOI: 10.1186/s40711-016-0034-1
|View full text |Cite
|
Sign up to set email alerts
|

Dating attitudes and expectations among young Chinese adults: an examination of gender differences

Abstract: While researchers have long examined the dating and mate selection patterns among young adults, the vast majority have utilized Western samples. In order to further our understanding of the changing nature of dating behaviors and attitudes, this study examines a sample of young Chinese adults and focuses upon the gender differences therein. Using a foundation of social exchange theory, the analyses illustrate the differences between the dating attitudes and expectations of Chinese women and men. Per traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…In our large sample that includes both dating and non-dating teens, girls' were generally more prone to depressive symptoms than boys, and their self-esteem was more strongly hampered by having a past relationship, consistent with previous studies which showed that girls are more likely to be negatively impacted by romantic involvement (Joyner & Udry, 2000;Natsuaki et al, 2009). Although previous studies suggested that Chinese girls hold more traditional sexual values than boys (Blair & Madigan, 2016;Li et al, 2010), we found that both boys' and girls' self-esteem were negatively related to sexual activities, possibly due to the ROMANCE AND ADJUSTMENT OF CHINESE ADOLESCENTS 22 overall conservative attitude towards sex in the Chinese societies where adolescent sex is nonnormative for adolescents of both sexesboth genders.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our large sample that includes both dating and non-dating teens, girls' were generally more prone to depressive symptoms than boys, and their self-esteem was more strongly hampered by having a past relationship, consistent with previous studies which showed that girls are more likely to be negatively impacted by romantic involvement (Joyner & Udry, 2000;Natsuaki et al, 2009). Although previous studies suggested that Chinese girls hold more traditional sexual values than boys (Blair & Madigan, 2016;Li et al, 2010), we found that both boys' and girls' self-esteem were negatively related to sexual activities, possibly due to the ROMANCE AND ADJUSTMENT OF CHINESE ADOLESCENTS 22 overall conservative attitude towards sex in the Chinese societies where adolescent sex is nonnormative for adolescents of both sexesboth genders.…”
Section: Discussionsupporting
confidence: 88%
“…The Chinese culture embeds romantic relationship in the larger frame of family lineage, and adolescents in traditional China entered arranged marriage with partners chosen by family seniors to extend patrilineal family lines instead of realizing individual romantic goals (Riley, 1994). Such values have been challenged since early 20 th century (Xu & Whyte, 1990), but the utilitarian view of romance as precursors leading to marriage and childbearing persists (Blair & Madigan, 2016;Liu, 2018), and Chinese parents remain heavily involved in their children's love lives (Sun, 2012). In addition, Chinese parents and teachers typically hold conservative values towards sex, resulting in lack of access to comprehensive sex education among Chinese adolescents (Cui, Li & Gao, 2001).…”
Section: Adolescent Romance In the Chinese Contextmentioning
confidence: 99%
“…Based on interviews with 19 Chinese college students, I explore how female and male participants use differing privacy management strategies in People Nearby-facilitated locative dating communication. I argue that gender power relations, which already exist in non-digital, heterosexual dating encounters between young Chinese people (Blair & Madigan, 2016), are invoked in locative dating communication as a result of their gendered navigation of the privacy paradox. This reveals how aspects of gender inequality are reproduced in the Chinese context of locative dating communication, by subjecting young Chinese women to greater restrictions when they attempt to capitalize on the dating opportunities offered by People Nearby.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, in the past two decades, there have been considerable cultural and institutional changes taking place in original countries for immigrant Asian populations. For example, the behaviors and values of the millennial generation of foreign‐born Chinese parents have been largely influenced by the one‐child policy in China (Blair & Madigan, ), as well as globalization and Westernization (Berman et al, ). Therefore, it is important to investigate whether the factor structure of AAFCS, a measurement developed around 1999, is still appropriate to measure the attitudes and practices of acculturation among current Chinese immigrant populations.…”
Section: Study Purposementioning
confidence: 99%